Effectiveness of Speaking English Practice on Procedural Text in ESP Classes for Automotive Engineering Students - Fauzi, Buyung Ramat; Rahmawati, Yeni; Ibrahim, Ibrahim (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study investigates the effectiveness of English-speaking practice through procedural texts in English for Specific Purposes (ESP) classes for automotive engineering students. Procedural texts, such as repair manuals and technical instructions, are integral to the automotive field and offer practical contexts for language learning. Using a one-group pre-test and post-test experimental design, 93 vocational students from SMKN 15 Samarinda East Kalimantan participated in structured speaking activities over five sessions. These included role-plays, peer feedback, and scenario-based practices using authentic automotive materials. Quantitative analysis using paired t-tests revealed a statistically significant improvement in students’ oral fluency scores, confirming the intervention’s effectiveness. The results suggest that engaging students with domain-specific procedural texts enhances both technical vocabulary acquisition and spoken communication skills. The study provides strong evidence for incorporating authentic materials and task-based speaking activities in ESP curricula, especially in vocational education contexts. It also supports the theoretical framework of task-based language teaching and highlights the value of contextualized learning for professional readiness.